La sexualidad y su influencia en las actitudes con sus pares en los estudiantes de sexto y séptimo grado de la Escuela de Educación Básica Prof. Floresmilo Rodríguez Arguello, de la ciudad de Machala, 2012-2013. - Riera Paz, Elsa Mary (2013)
Sexuality is all that makes us unique, such as the way we feel to speak, to express our feelings, which we like, what we dislike. Sexuality is part of our lives from cradle to grave.